Single Molecule Measurements of Interaction Free Energies Between the Proteins Within Binary and Ternary SNARE Complexes - Liu, W. (2009)
We use an Atomic Force Microscope based single molecule measurements to evaluate the activation free energy in the interaction of SNARE proteins syntaxin 1A, SNAP25B and synaptobrevin 2 which regulate intracellular fusion of vesicles with target membranes. The dissociation rate of the binary syntaxin-synaptobrevin and the ternary syntaxin-SNAP25B-synaptobrevin complex was measured from the rupture force distribution as a function of the rate of applied force. The temperature dependence of the spontaneous dissociation rate was used to obtain the activation energy to the transition state of 19.8 ± 3.5 kcal/mol = 33 ± 6 k(B)T and 25.7 ± 3.0 kcal/mol = 43 ± 5 k(B)T for the binary and ternary complex, respectively. They are consistent with those measured previously for the ternary complex in lipid membranes and are of order expected for bilayer fusion and pore formation. The ΔG was 12.4–16.6 kcal/mol = 21–28 k(B)T and 13.8–18.0 kcal/mol = 23–30 k(B)T for the binary and ternary complex, respectively. The ternary complex was more stable by 1.4 kcal/mol = 2.3 k(B)T, consistent with the spontaneous dissociation rates. The higher adhesion energies and smaller molecular extensions measured with SNAP25B point to its possible unique and important physiological role in tethering/docking the vesicle in closer proximity to the plasma membrane and increasing the probability for fusion completion.